(untitled) (Indian Journal of Public Health Research & Development, 2020)
Objectives: Plasmodium vivax is a type of Plasmodium that is difficult to eliminate because it has a hypnozoite phase in the human liver and responsible for malaria recurrence[1]. Health education is one of method that can be used to improve adherence to primaquine treatment. In doing so, the vivax malaria recurrence rate can be decreased significantly. The aim of this study was to examine the effectiveness of health education in reducing Plasmodium vivax malaria recurrence. Method: A quasi-experimental method was conducted in January-August 2019 at Sentani Papua. Patients from community health care had been diagnosed with P.vivax malaria by microscopy, age ? 1 year, treated according to national standards with DHP for 3 days and primaquine 14 days, were recruited. Patients were divided into 2 groups, namely, the standard therapy group (ST) and the standard therapy group with health education (HE) group. Then patients were followed-up for 90 days. Results: Among 105 patients, 50 were in the ST group and 55 were in the HE group. Patients recovered without serious adverse effects. The incidence rate of recurrence in the HE group was much lower compared to the ST group (2.04/10,000 person-days vs 21.51/10,000 person-days, p <0.05). The risk of recurrence was 9 times higher among patients from ST group compare to HE group (AHR =9.44, 95% CI: 1.2-78.0). Conclusion: The existence of health education by health workers after the administration of standard drugs is effective in increasing adherence to 14 days of primaquine treatment to prevent the recurrence of P. vivax malaria. The reduction in P. vivax malaria recurrence is in line with the reduced malaria transmission and morbidity in endemic areas.